High-Entropy Oxides Fundamental Aspects and Electrochemical Properties - Sarkar, Abhishek (Advanced materials (Deerfield Beach, Fla.), 2019)
© 2019 The Authors. Published by WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.